2008
DOI: 10.1016/j.worlddev.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Wages and Poverty in a Developing Country: Simulations from Indonesia’s Household Survey

Abstract: This study focuses on the efficiency of minimum wage policy for poverty reduction, taking Indonesia as a case study. A simulation approach assesses who benefits and who pays for minimum wage increases. On the benefits side, the rise in minimum wages boosts incomes in households with low wage workers. However, increases in wage costs are passed on through higher consumer prices. As a result, three out of four poor households lose in net terms, even when we assume no job losses. The findings suggest that minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 14 publications
1
31
0
6
Order By: Relevance
“…Based on the regression equations, at the point where maximum diversity is conserved, an annual gross income per 0.1 ha of approximately IDR 3.3 million (US$ 287; US$1 = IDR 11,500 in February 2009) can be generated, or approximately IDR 2.3 million (US$200) if bamboo-dominated gardens are excluded. That amount, however, is not a sufficient minimum income in Indonesia (the per capita income of US$2 a day as the adjusted poverty line: Bird and Manning 2008). The gardens are useful for subsistence purposes to obtain various products, such as fruits, timber, and fuelwood, but not as a primary source of monetary income.…”
Section: Optimizing Profitability and Agrobiodiversitymentioning
confidence: 99%
“…Based on the regression equations, at the point where maximum diversity is conserved, an annual gross income per 0.1 ha of approximately IDR 3.3 million (US$ 287; US$1 = IDR 11,500 in February 2009) can be generated, or approximately IDR 2.3 million (US$200) if bamboo-dominated gardens are excluded. That amount, however, is not a sufficient minimum income in Indonesia (the per capita income of US$2 a day as the adjusted poverty line: Bird and Manning 2008). The gardens are useful for subsistence purposes to obtain various products, such as fruits, timber, and fuelwood, but not as a primary source of monetary income.…”
Section: Optimizing Profitability and Agrobiodiversitymentioning
confidence: 99%
“…Particularly, Rama (2001) and Suryahadi et al (2001) show that minimum wage hikes have a positive impact on average wages of all workers and all segments of the workforce but are mostly insignificant except for the sub-sample of blue-collar workers. On the contrary, using the simulation framework, Bird and Manning (2008) report negative effects of the policy on wages in the informal sector.…”
Section: Introductionmentioning
confidence: 96%
“…A recent World Bank (2010) study corroborated this result for women but found the opposite for skill. Bird and Manning (2008) concluded that while most households with a lowwage, formal-sector worker benefit from higher minimum wages, the majority of the working poor are engaged in the informal sector and therefore face higher prices but receive no wage compensation. Furthermore, Chun and Khor (2010) found no evidence that wages in the informal sector increase in response to a rise in minimum wages in the formal sector.…”
Section: Who Bears the Cost Of Minimum-wage Increases?mentioning
confidence: 99%